Polycystic ovary syndrome (PCOS): progress towards a better understanding and treatment of the syndrome - Mimouni, Nour El Houda; Giacobini, Paolo (Comptes Rendus Biologies)
Polycystic ovary syndrome (PCOS) is the most common endocrine and metabolic disorder in women of reproductive age. It has a strong hereditary component estimated at 60 to 70% in daughters. It has been suggested that environmental factors during the fetal period may be involved in the development of the syndrome in adulthood. However, the underlying mechanisms of its transmission remain unknown, thus limiting the development of effective therapeutic strategies.This article highlights how an altered fetal environment (prenatal exposure to high levels of anti-Müllerian hormone) can contribute to the onset of PCOS in adulthood and lead to the transgenerational transmission of neuroendocrine and metabolic traits through alterations in the DNA methylation process.The originality of the translational findings summarized here involves the identification of potential biomarkers for early diagnosis of the syndrome, in addition to the validation of a promising therapeutic avenue in a preclinical model of PCOS, which can improve the management of patients suffering from the syndrome.